Anonymous
Topics: Science
The mathematical expression x^6 - 2 x^3 + 1 can be factored to (x^3 - 1)^2, and, if set equal to 0, it has roots x=1, x=-(-1)^(1/3), and x=(-1)^(2/3).
Sure! Divide both sides by 6, then you have x = 5. Thank you for asking today!
x=36. You would first devide 3/4=.75. Then divide .75 both sides, making x=36....
The answer to a= 1/2 bh is A=1/2bh --> b = 2A / h. !
Yes, (1/5) x3 + (1/2) x is a polynomial.
The expression x^3 + 5x^2 - 36x - 180 = 0 simplifies to (x + 5) (x^2 - 36) = 0 so...
Google is -paying 97$ per hour!...
The earthworms excrete nitrogenous waste similar to urine from pores all along...
HaeIII cuts at the sequence GGCC. This nucleotide sequence is found between...
One M&M is .636 cubic centimeters. M&Ms have a packing density of 68%. Volume/size...
Phytoplanktons are basically tiny living algae that are seen floating on the...